Sound absorption coefficient from composites made from coconut fiber, paper, and styrofoam - Amalia Ma'rifatul Maghfiroh (University of Muhammadiyah Malang, 2024)
Noise is an unpleasant/undesirable sound. Apart from noise, environmental problems are often faced by the community in the form of organic and inorganic waste resulting from several small/large industrial activities. Organic waste often encountered is young coconut fiber from activities in traditional markets. Paper waste comes from teaching and learning activities/offices. Styrofoam waste is included in the category of inorganic waste, which is very difficult to decompose, so it has a bad impact on the environment. Based on this, a composite was made from coconut fiber, paper and styrofoam so that it could be used as a sound absorber. Cylindrical composite specimens were made with different variations in composition and analyzed the differences in sound dampening ability in various compositions. The sound absorption capacity of the composite was measured at frequencies of 125 Hz, 250 Hz, 500 Hz, 750 Hz, 1,000 Hz, 2,000 Hz and 4,000 Hz. The composite acoustic test results obtained for samples A, B and C showed that the highest absorption energy was 49.57 dB at a frequency of 750 Hz for sample C. Meanwhile, the lowest absorption energy was 1.15 dB at a frequency of 500 Hz for sample A. The sound absorption coefficient values ​​were obtained for all variations. The frequencies of samples A, B and C have good absorption coefficient values, namely ≥ 0.2. The lowest absorption coefficient value was 2.01 at a frequency of 750 Hz for sample C and the highest was 46.67 at a frequency of 500 Hz for sample A.